Factors Associated With Short-Term Eradication of Rectal Colonization by KPC-2 Producing Klebsiella pneumoniae in an Outbreak Setting - Pellicé, Martina; Rodríguez-Núñez, Olga; Rico, Verónica; Agüero, Daiana; Morata, Laura; Cardozo, Celia; Puerta-Alcalde, Pedro; Garcia-Vidal, Carolina; Rubio, Elisa; Fernandez-Pittol, Mariana J.; Vergara, Andrea; Pitart, Cristina; et al. (Frontiers in Microbiology, 2021)
Background: KPC-producing Klebsiella pneumoniae (KPCKP) is a threat for patients admitted to healthcare institutions. In this study, we assess the efficacy of several decolonization strategies for KPCKP rectal carriage. Methods: Observational study performed during an outbreak of KPCKP on the efficacy of a 10-day non-absorbable oral antibiotic (NAA) regimen (colistin 10 mg/L, amikacin 8 mg/mL and nystatin 30 mg/mL, 10 mL/6 h) vs the same regimen followed by a probiotic (Vivomixx®) for 20 days. Results: Seventy-three patients were included, 21 patients (29%) did not receive any treatment and 52 (71.2%) received NAA either alone (n=26, 35.6%) or followed by a probiotic (n=26, 35.6%). Eradication was observed in 56 (76.7%) patients. The only variable significantly associated with it was not receiving systemic antibiotics (22/24 [91.6%] vs 34/49 [69.3%], p=0.04). Eradication in patients receiving NAA plus probiotic was numerically but not significantly higher than control (23/26 [88.4%] vs 15/21 [71.4%], p=0.14) and of those receiving only NAA (OR 3.4, 95% CI 0.78-14.7, p=0.09). Conclusion: KPCKP colonization persisted after a mean of 36 days in only about one quarter of colonized patients. A 10-day course of NAA had no impact on eradication. Probiotics after NAA may increase the decolonization rate.